2018
DOI: 10.1038/s41598-017-18360-4
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy Needle Integrated with Electrical Impedance Sensing Microelectrode Array towards Real-time Needle Guidance and Tissue Discrimination

Abstract: A biopsy needle with electrical impedance sensor array based on stainless steel microelectrodes (EIS needle) was developed for real-time four electrode measurement and multi-spot sensing of tissues during the biopsy process. The sensor performance was characterized by using saline solutions with various concentrations, which proved accurate, stable and reliable electrical impedance measurement. The capability of impedance-based tissue sensing was verified by the conductivity measurement of agarose hydrogel bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 32 publications
0
66
0
Order By: Relevance
“…Such a diagnostic tool can complement well-established methods, mainly those investigating the effects of drug therapy or evaluating the malignancy degree via the cancerous cell growth rate. 10 Furthermore, it has been recently demonstrated that bioimpedance techniques could possibly be adopted in clinical practise as well, [11][12][13][14] for example in testing the health status of the cells extracted from a biopsy. However, the introduction of our method in common clinical practice (based on ex vivo cells) will require further investigation for the implementation of the cell interdigitated electrodes device and for modeling calculation and subsequent univocal criterion for the assignment of the estimated electrical parameters to the cellular status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a diagnostic tool can complement well-established methods, mainly those investigating the effects of drug therapy or evaluating the malignancy degree via the cancerous cell growth rate. 10 Furthermore, it has been recently demonstrated that bioimpedance techniques could possibly be adopted in clinical practise as well, [11][12][13][14] for example in testing the health status of the cells extracted from a biopsy. However, the introduction of our method in common clinical practice (based on ex vivo cells) will require further investigation for the implementation of the cell interdigitated electrodes device and for modeling calculation and subsequent univocal criterion for the assignment of the estimated electrical parameters to the cellular status.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Moreover, recent studies have demonstrated the possible adoption of electrical bioimpedance into clinical practice. [11][12][13][14] Until now, extensive literature has been focused on characterizing the electrical impedance of cells and formulating electrical models, which simulate cellular electrical responses. 15 The study of cells real-time impedance has been also performed by introducing specific methods for the cellular electrical response.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have attempted to characterize different biological tissues using needle-type electrodes [ 15 , 26 , 27 , 28 ]. However, we used a non-invasive concentric ring-type surface electrode as a novel approach for measuring oral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A dielectric property is, therefore, associated with biological tissue wherein the relative permittivity reduces with increasing frequency [10]. Previous studies reported the monopolar, bipolar, or quadripolar microelectrode integrated needle using impedance measurement for the tissue characterization [3,[11][12][13][14][15][16]. The microelectrode based impedance measurement showed the possibility of tissue discrimination with needle guidance [3,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The microelectrode based impedance measurement showed the possibility of tissue discrimination with needle guidance [3,13,14]. Park et al presented the impedimetric sensor based biopsy needle for the detection and extraction of suspected cancerous tissues [15]. Halonen et al introduced the novel Injeq IQ-Biopsy needle for real-time tissue identification and discrimination by FEM simulation and biopsy experiment with 21 punctures in five tissue types [17].…”
Section: Introductionmentioning
confidence: 99%